Identification and Functional Analysis of the Mycophenolic Acid Gene Cluster of Penicillium roqueforti - Del-Cid, Abdiel; Gil-Durán, Carlos; Vaca, Inmaculada; Rojas-Aedo, Juan F.; García-Rico, Ramón O.; Levicán, Gloria; Chávez, Renato (PloS one, 2016)
The filamentous fungus Penicillium roqueforti is widely known as the ripening agent of blue-veined cheeses. Additionally, this fungus is able to produce several secondary metabolites, including the meroterpenoid compound mycophenolic acid (MPA). Cheeses ripened with P. roqueforti are usually contaminated with MPA. On the other hand, MPA is a commercially valuable immunosuppressant. However, to date the molecular basis of the production of MPA by P. roqueforti is still unknown. Using a bioinformatic approach, we have identified a genomic region of approximately 24.4 kbp containing a seven-gene cluster that may be involved in the MPA biosynthesis in P. roqueforti. Gene silencing of each of these seven genes (named mpaA, mpaB, mpaC, mpaDE, mpaF, mpaG and mpaH) resulted in dramatic reductions in MPA production, confirming that all of these genes are involved in the biosynthesis of the compound. Interestingly, the mpaF gene, originally described in P. brevicompactum as a MPA self-resistance gene, also exerts the same function in P. roqueforti, suggesting that this gene has a dual function in MPA metabolism. The knowledge of the biosynthetic pathway of MPA in P. roqueforti will be important for the future control of MPA contamination in cheeses and the improvement of MPA production for commercial purposes.